(untitled) (Patan Pragya, 2025)
This paper explores the Hindu festival of Krishna Janmashtami in Nepal, examining its religious significance, ritual practices, regional variations, and socio‐economic impacts. This paper has employed an exploratory design. Drawing on a variety of published sources and festival-reports, the paper illustrates how this celebration of the birth of Lord Krishna manifests differently across Mahotari district, how such rituals contribute to community identity in Suga Village, and how the festival influences local economies and commercial activity. The findings suggest that while the core religious narrative remains consistent, diverse regional cultural forms and growing commercialization are shaping how Krishna Janmashtami is experienced in Suga Village. Implications for cultural preservation and festival-economy balance are discussed. Besides, the huge participation of people from all walks of life in making the festival a grand success reflects the community engagement and devotion of the practicing Hindus in the rural Nepal as exemplified by Suga Village. The continuity of tradition enhances the flavor of the past and beauty of communal gathering and bonding is intensified. The communal reinforcement for participation and contribution makes the community unity exemplary as experienced by the participants in Krishna Janmasthtami Festival in Suga Village. The researcher has used the qualitative research design and has analyzed the contents drawn from different secondary sources and has integrated the secondary data with the primary knowledge based on personal observation and participation in the festival.